Sexual Behaviors and Sexually Transmitted Infections Among Male Veterans and Nonveterans. (July 2017) - Evans, Mark W.; Borrero, Sonya; Yabes, Jonathan; Rosenfeld, Elian A.
Little is known about the sexual health of male veterans. This study used nationally representative data from the 2011 to 2013 National Survey of Family Growth to compare sexual behaviors and history of sexually transmitted infections (STIs) between male veterans and nonveterans. The sample included 3, 860 men aged 18 to 44 years who reported ever having sex with a man or woman. The key independent variable was veteran status. Sexual behavior outcomes included ≥6 lifetime female partners, ≥10 lifetime partners of either sex, ≥2 past-year partners of either sex, having past-year partners of both sexes, and condom nonuse at last vaginal sex. STI outcomes included past-year history of chlamydia, gonorrhea, or receiving any STI treatment; lifetime history of herpes, genital warts, or syphilis; and an aggregate measure capturing any reported STI history. Logistic regression models were used to evaluate associations between veteran status and each outcome. In models adjusting for age, race/ethnicity, education, income, and marital status, veterans had significantly greater odds than nonveterans of having ≥6 lifetime female partners ( OR = 1.5, 95% CI [1.02, 2.31]). In models adjusting for age and marital status, veterans had significantly greater odds of having partners of both sexes in the past year ( OR = 4.8, 95% CI [1.2, 19.8]), and gonorrhea in the past year ( OR = 3.2, 95% CI [1.2, 8.5]). Male veterans were thus significantly more likely than nonveterans to have STI risk factors. Health care providers should be aware that male veterans may be at higher risk for STIs and assess veterans' sexual risk behaviors.